Relationship between family policies and fertility changes in Japanese municipalities - Shigeki Matsuda; Kenji Kamata (Social Sciences and Humanities Open)
Japan has been implementing family policies to restore fertility. Its municipalities provide residents with family policies under a government-created system. However, many municipalities offer additional family policies that often differ between municipalities. This study explored the relationship between family policies by municipalities and fertility rate changes from the mid-2000s to mid-2010s. The data used were from a sample survey conducted for municipalities, combined with regional data divided by municipality (N = 568). The data were analyzed using multiple regression analysis. In municipalities with relatively large populations, the higher the number of implemented measures, the higher the fertility rate change. This relationship was observed for approximately 5–10 years after the implementation of the family policy. These results suggest that implementing various measures by Japanese municipalities to support different types of families may have contributed to the increase in total fertility rate, and that it took some time for the family policies to affect total fertility rate.